Study of the useful characteristics of the red pigments of Serratia marcescens strains isolated from the soil - Ritasree Mandal, Arindam Adhikari, Gopinath Rana, Tanusri Mandal (Journal of Applied Pharmaceutical Science, 2017)
Two red pigments have been produced by two different bacterial strains. They have been isolated from soil of West Bengal, India. Upon biochemical and the 16s rRNA analysis, the two strains have been identified as Serratia marcescens by the NCBI (National Center for Biotechnology Information). The GenBank accession number of one of the strains named PNSRR is KU726553. Another one, PNSHR, has the GenBank accession number, KU707218. Maximum red pigment productions have been achieved by optimizing the physical parameter, temperature, and also the chemical parameters, such as pH and Magnesium Chloride (MgCl2) catalyst. The two red pigments have been extracted from two different bacteria by methanol extraction procedure. Those pigments have been identified as prodigiosin, when passed them through HPLC and UV-Vis spectrometry. The Rf values of the extracted pigments have been found to be around 0.88 in the TLC method. The lower IC50 values of the pigments have demonstrated stronger antioxidant activities than the conventional ones, such as ginger, turmeric, and garlic. In addition, they have antibacterial activities against E. coli and K. pneumoniae. Specifically, the strain, KU726553, has shown strong dye activity, when used in cotton and plastic materials.
Keywords: Serratia marcescens, Red pigments, prodigiosin, 16s rRNA analysis, Antioxidant, Antibacterial.